Second Account Instagram sebagai Media Self Disclosure di Kalangan Mahasiswa - Anggraini, Rahma Dini; Ardiyansyah, Ardiyansyah; Aminah, Siti; Nurkhayati, Ayu (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Social media is a means for self-disclosure or self-disclosure. Instagram is a social media that is a means for self-disclosure, through the features of the Instagram application, students can share photos, videos, stories and other content to show aspects of their lives to other people. Not a few students of the Islamic Communication and Broadcasting Study Program of the Sulthan Thaha Saifuddin Jambi State Islamic University use a second Instagram account for several reasons, including because they have more freedom to open themselves on this account which only selected people can access. access it. The research method used is descriptive qualitative. Data collection was carried out using observation, interviews and documentation techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of research conducted on 12 (twelve) student informants can be concluded that the self-disclosure that tends to be highlighted is self-disclosure in open areas, blind areas and hidden areas.